2012
DOI: 10.1186/1471-2164-13-568
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of single nucleotide polymorphism among 27 diverse alfalfa genotypes as assessed by transcriptome sequencing

Abstract: Background: Alfalfa, a perennial, outcrossing species, is a widely planted forage legume producing highly nutritious biomass. Currently, improvement of cultivated alfalfa mainly relies on recurrent phenotypic selection. Marker assisted breeding strategies can enhance alfalfa improvement efforts, particularly if many genome-wide markers are available. Transcriptome sequencing enables efficient high-throughput discovery of single nucleotide polymorphism (SNP) markers for a complex polyploid species. Result: The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
50
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 44 publications
5
50
0
1
Order By: Relevance
“…Minimal diversity appeared to have been lost in cultivated tetraploid alfalfa compared to wild diploid alfalfa based on a transcriptome analysis of 27 genotypes [19]. In this study, we genotyped a larger population of individuals with the SNP array and found a similar result.…”
Section: Discussionsupporting
confidence: 54%
“…Minimal diversity appeared to have been lost in cultivated tetraploid alfalfa compared to wild diploid alfalfa based on a transcriptome analysis of 27 genotypes [19]. In this study, we genotyped a larger population of individuals with the SNP array and found a similar result.…”
Section: Discussionsupporting
confidence: 54%
“…This species is a perennial, cross-pollinated and autotetraploid (2n ¼ 4x ¼ 32) plant with a genome size of 800e900 Mb (Choi et al, 2004). Extensive efforts have been made to develop alfalfa transcriptome data, including 454 sequencing (Han et al, 2011) and Illumina sequencing (Li et al, 2012;Liu et al, 2013;Postnikova et al, 2013;Yang et al, 2011), which have facilitated the development of transcript-based molecular markers for alfalfa, such as expressed sequence tag simple sequence repeat markers (EST-SSRs).…”
Section: Introductionmentioning
confidence: 99%
“…Annotation of assembled RNASeq reads can help in understanding the function of a gene or a transcript. Annotations have been used in several crops for establishing genetic information where limited knowledge exists (Garg et al 2011; Li et al 2012). SNPs in annotated transcripts associated with traits would benefit functional characterization of genes.…”
mentioning
confidence: 99%